2017
DOI: 10.18203/2320-6012.ijrms20172444
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of clonidine versus nalbuphine as intrathecal adjuvants to 0.5% hyperbaric bupivacaine for subarachnoid block during gynaecological procedures: a double blind study

Abstract: Background: Regional anesthesia techniques for gynaecological procedures are on increasing trends due to their advantage of postoperative analgesia owing to intrathecal adjuvants. The present study was aimed to comparatively evaluate the clinical efficacy of clonidine with nalbuphine when co-administered intrathecally with 0.5% hyperbaric bupivacaine for gynaecological procedures.Methods: Regional anesthesia techniques for gynaecological procedures are on increasing trends due to their advantage of postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 8 publications
5
8
0
Order By: Relevance
“…In the present study, the clonidine and nalbuphine were used as intrathecal adjuvant to hyperbaric bupivacaine, which revealed that statistically highly significant difference for onset of sensory block (p<0.001) and onset of motor block (p<0.001) between both the groups. The onset of sensory and motor blockade was earlier with intrathecal nalbuphine while duration of motor blockade was more prolonged by intrathecal clonidine as compared to intrathecal nalbuphine which was statistically highly significant (p<0.001), these results were also similar found by Bansal M. et al (9) These effects showed synergism between bupivacaine and intrathecal adjuvants.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, the clonidine and nalbuphine were used as intrathecal adjuvant to hyperbaric bupivacaine, which revealed that statistically highly significant difference for onset of sensory block (p<0.001) and onset of motor block (p<0.001) between both the groups. The onset of sensory and motor blockade was earlier with intrathecal nalbuphine while duration of motor blockade was more prolonged by intrathecal clonidine as compared to intrathecal nalbuphine which was statistically highly significant (p<0.001), these results were also similar found by Bansal M. et al (9) These effects showed synergism between bupivacaine and intrathecal adjuvants.…”
Section: Discussionsupporting
confidence: 86%
“…In present study, the mean time to two segment regression and time to first rescue analgesic request was significantly delayed in patients of clonidine group when compared to nalbuphine group. Similar results were also observed by Bansal M. et al (9) and Chetty D.K. et al (10) This was also in accordance to the study of Tilker Y et al (5) , Elia N et al (2) and Stebral S et al (4) who also reported that the time taken for regression of sensory block and time of first rescue analgesia were statistically more in patients of clonidine group than 0.5% bupivacaine alone and to the study of Clubras X et al (3) and Fareed A. et al (7) who were found that the time of two segment regression and time of first rescue analgesia also prolonged with intrathecal nalbuphine as compared to control group.…”
Section: (9)supporting
confidence: 91%
See 1 more Smart Citation
“…However, it is comparable between nalbuphine and clonidine while Bansal et al . [ 23 ] demonstrated faster onset of sensory and motor block due to nalbuphine.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated no clinically significant difference in the hemodynamic parameters and adverse effects (nausea, vomiting, and pruritus) among the three groups, supported by Bansal et al . [ 23 ] Low-dose clonidine is not associated with hemodynamic instability as evidenced by Dutta et al . [ 21 ] Opioid-related side effects were not encountered significantly in nalbuphine group due to its mu (μ)-antagonist property.…”
Section: Discussionmentioning
confidence: 99%